Madrasah Sebagai Pilihan Orang Tua Bagi Pendidikan Anak di Madrasah Ibtidaiyah Ma’arif 01 KH. Shiddiq Jember - Suryadi Suryadi; Wike Silfia (JIP Jurnal Ilmiah PGMI, 2019)
ABSTRACT This paper adopts researchers through the phenomenon of students' parents wanting to educate their children as a choice of Madrasah Ibtidaiyah in the hope that their children have deep religious knowledge, have sufficient knowledge as a provision of life and their pupils have the desired achievements at school. Madrasah Ibtidaiyah is a formal Islamic Basic Education Institution at the elementary school level where the learning process involves an educational process about religion that serves to instill religious values ​​towards students. Madrasah Ibtidaiyah Ma’arif 01 KH. Shiddiq Jember or also known as MIMA 01 KH. Shiddiq is one of the schools or madrassas which is a favorite choice for the people of Jember because in it teaches Islamic-based basic education which has learning that is almost the same as Islamic primary schools in general. The research approach that researchers use is a qualitative approach to the type of descriptive qualitative research. Data collection by non-participatory observation, unstructured interviews and documentation and data analysis techniques using Miles and Huberman; data reduction, presentation of data and drawing conclusions. The results of this study are: 1. Factors and motivations of the community to choose Madrasah Ibtidaiyah Ma'arif 01 KH. Shiddiq Jember as a place of education for their children there are two factors: 1) intrinsic factors which include: a. parents have awareness of the need for values ​​of Religious Education; b. The knowledge and education of parents and the ideals or expectations of all guardians of students so that their children can learn general knowledge and religion at school. 2) extrinsic factors include: a. the availability of facilities & infrastructure and accompanied by a religion-based curriculum; b. The cost is relatively affordable for the middle to lower classes; c. There is a good supervision conducted in the learning process; d. The curriculum used by educators in the learning process is the same as the curriculum in public schools and is supplemented by religious education; e. Hoping to get blessings, benefits and knowledge from KH. Shiddiq. Keywords: Madrasa As a Choice of Parents, Child Education, Madrasah Ibtidaiyah Ma’arif 01 KH. Shiddiq Jember.